Pengaruh E-wom dan Promosi di Media Sosial terhadap Keputusan Pembelian Produk Somethinc - Karim, Abdul Razak; Dara, Siti Ruhana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The aim of this research is to determine the influence of electronic word of mouth variables through promotions on social media. The use of social media to market products is very interesting to observe, especially in terms of looking at customer behavior. The sample for this research is consumers who have purchased Somethinc products, who have seen promotions on social media about Somethinc products and are active followers of Somethinc social media. The sample for carrying out this research test was 100 people who were calculated using the hair formula. Data analysis uses validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, f tests and t tests. The results of the following research show that the electronic word of mouth variable has a significant influence on purchasing decisions. Social media promotion has a significant influence on purchasing decisions. The influence variables of electronic word of mouth and promotions on social media jointly influence purchasing decisions. Suggestions for Somethingc to improve e-WOM, promotions on social media to increase purchasing decisions.